Phytochemical profile of sugarcane and its potential health aspects - Singh, Amandeep; Lal, Uma Ranjan; Mukhtar, Hayat Muhammad; Singh, Prabh Simran; Shah, Gagan; Dhawan, Ravi Kumar (Pharmacognosy Reviews)
Sugarcane (Saccharum officinarum Linn.) is an important perennial grass of Poaceae family, indigenous to tropical South Asia and Southeast Asia. It is cultivated worldwide due to the economical and medicinal value of its high yielding products. Sugarcane juice is well known as a raw material for the production of refined sugar and its wax is considered as a potential substitute for the expensive carnauba wax, which is of cosmetic and pharmaceutical interest. Refined sugar is the primary product of sugarcane juice, but during its processing, various other valuable products are also obtained in an unrefined form, such as, brown sugar, molasses, and jaggery. Sugarcane juice is widely used in India in the treatment of jaundice, hemorrhage, dysuria, anuria, and other urinary diseases. Herein, we have summarized the different phytoconstituents and health benefits of sugarcane and its valuable products. The phytochemistry of sugarcane wax (obtained from the leaves and stalks of sugarcane), leaves, juice, and its products has revealed the presence of various fatty acid, alcohol, phytosterols, higher terpenoids, flavonoids, ‑O‑ and ‑C‑glycosides, and phenolic acids. The future prospective of some of the sugarcane products has been discussed, which needs a phytopharmacological study and has a great potential to be a valuable medicinal product.
Keywords: Fatty acid; phenolic acids; phytochemistry; Saccharum officinarum